Оцінка дальності дії тепловізійного каналу при виявленні БПЛА - Сидоренко, Е. В. (ХНУРЕ, 2021)
The evaluation of the UAV detection range limited by the noise of the thermal imager is performed in the work. To determine the signal-to-noise ratio according to the formulas, the following initial data were taken: a model describing the dispersed composition of continental temperate air in the summer season; spectral range of heat waves, absolute humidity, meteorological visibility, maximum length of the route. It is shown that the sensitivity of most modern thermal imagers is sufficient to detect UAVs at distances greater than 3 km. Therefore, the main limiting factor is the fulfillment of Johnson's criterion.
Keywords: БПЛА; тепловізійний канал